CONFLICT OF INTEREST IN ADMINISTRATIVE LAW - Elena Emilia ȘTEFAN (Challenges of the Knowledge Society)
We are currently witnessing, on the one hand, new forms of relationships between public and private sector, such as public-private partnership agreements, concession agreements, etc. and on the other hand, the expectations of citizens towards public authorities are increasingly higher in what concerns the lawfulness and transparency of their activities in terms of protecting citizen’s interest. Therefore, in this study, we aim to analyze how the conflict of interest is regulated within the area of the administrative law and to present the new conception of the lawmaker in what concerns this topic, taking into account the European tendencies.